The parental negligence and relationship with disabilities: what does the national survey shows - Mara Silvia Pasian (Universidade Federal de Santa Maria (UFSM), 2015)
Child maltreatment can cause several negative consequences for development, and, in certain situations, can be generated for any deficiency that child from neglect or violence generated against it, and some cases may lead to death. The objective of this study was to investigate material published in the Brazil involving the theme of maltreatment and child, specifically in the form of child neglect and somehow that addressed the terms disabilities or special needs. For this was made a search in databases and SCIELO LILACS, without restriction period, the articles selected are between the years 2000 and 2010. Then were selected and analyzed qualitatively 12 full articles. The results of this research show that the analyzed articles centered on the theme of the description of the types of abuse and the need for increased awareness and reporting of cases involving child abuse, two articles address the relationship of child maltreatment and disability, showing significant vulnerability of children with disabilities for the occurrence of parental abuse or neglect. The considerations point to the need research production and dissemination of studies involving the issue of child neglect and the individual with special needs, focusing consequences and prevention measures.